Keys to the Car: Driving Cessation and Residential Location Among Older Adults. Issue 1 (2nd January 2022) - Schouten, Andrew; Blumenberg, Evelyn; Wachs, Martin; King, Hannah
Abstract: Problem, research strategy, and findings: Most Americans live in communities in which automobiles are central to participation in economic, social, and cultural activities. Outside of dense central cities, the ability to continue driving as one ages is fundamental to the quality of life among older adults. Driving rates decline significantly with age. Researchers have studied the myriad reasons former drivers stop driving, but few have examined associations between these transitions and characteristics of the neighborhoods in which older adults live or to which they move. We used longitudinal data from a national sample of 20, 000 observations from the University of Michigan Health and Retirement Study (HRS) to examine relationships between residential location, driving reduction, and driving cessation. Longitudinal data allow analysis of changes in behavior, a major advantage over cross-sectional data; however, the timing and sequencing of behavioral changes remain difficult to isolate. Cities provide opportunities for older adults to travel by automobile and other modes that are less available outside cities. Older adults are more likely to reduce or give up driving if they reside in dense, urban, transit-oriented neighborhoods than other neighborhood types. Very few older adults move from suburban to urban neighborhoods; when they do, they are rarely more likely to reduce or stop driving. Takeaway for practice: The findings underscore the importance of planning to accommodate aging in place. To do this in urban neighborhoods, policies must foster high-quality urban neighborhoods that not only attract younger adults (as is currently the trend) but also retain them as they age through the life cycle.